Travel Constraints and Willingness to Pay During a Global Crisis: Lessons from South African Domestic Tourism - Tafadzwa Matiza; Elmarie Slabbert (Studia Periegetica)
Academic inquiry into the impact of crises on the behaviour of domestic tourists is still relatively new, which justifies further research into the impact of the COVID-19 pandemic on domestic tourism. The following study explores the potential mediating effect of travel constraints experienced by South African tourists and their willingness to pay for tourism services on how pandemic-induced risks affect their tourism motivations. Data collected from 427 respondents indicate that the crisis caused by the pandemic has brought about a shift in the psychographic characteristics of South African domestic tourists, as evidenced by a statistically significant partial serial mediation of intrinsic constraints and willingness to pay in the relationship between pandemic-induced physical risk and outdoor recreational tourism motivations. The findings provide baseline data for a demand-driven domestic tourism policy and can be used to develop a strategy for the short-to-medium term.